1975
DOI: 10.1161/01.cir.52.5.909
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantitation of myocardial infarction with technetium 99m pyrophosphate.

Abstract: SUMMARYWe sought to quantitate infarct size using radioactive imaging techniques. Infarcts were created in closed chest dogs. Using a scintillation camera interfaced to a computer, infarct images were made in the anterior, left lateral, LAO, and RAO projections, 48 Fourteen mongrel dogs weighing 14 to 31 kg were anesthetized with intravenous sodium pentobarbital (5 mg/kg). Via a carotid approach, utilizing a modified coaxial catheter and a closed chest technique,"' we selectively embolized small occluded cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Thus, the thesis that positive mTc-PYP myocardial scintigrams in subjects with acute myocardial infarcts result primarily from visualization of high levels of 9mTc-PYP in necrotic myocardium is supported by the findings in this study as well as by: (a) the close correlation between estimates of infarct size obtained from measurements of infarct area on mTc-PYP myocardial scintigrams and morphologically determined infarct size in dogs with proximal LAD occlusion (46,47); (b) the findings of Martonffy et al (48) indicating that significant 'mTc-PYP concentration occurs only after intervals of ischemia which produce myocardial necrosis in the canine left circumflex coronary occlusion model (28,38); and (c) the characteristic time course of positive "mTc-PYP myocardial scintigraphy, with positive myocardial scintigrams being observed between 12-16 h and 7-14 days after experimental LAD occlusion or clinical onset of infarction (16)(17)(18)(19)(20)35).…”
Section: Tsupporting
confidence: 65%
“…Thus, the thesis that positive mTc-PYP myocardial scintigrams in subjects with acute myocardial infarcts result primarily from visualization of high levels of 9mTc-PYP in necrotic myocardium is supported by the findings in this study as well as by: (a) the close correlation between estimates of infarct size obtained from measurements of infarct area on mTc-PYP myocardial scintigrams and morphologically determined infarct size in dogs with proximal LAD occlusion (46,47); (b) the findings of Martonffy et al (48) indicating that significant 'mTc-PYP concentration occurs only after intervals of ischemia which produce myocardial necrosis in the canine left circumflex coronary occlusion model (28,38); and (c) the characteristic time course of positive "mTc-PYP myocardial scintigraphy, with positive myocardial scintigrams being observed between 12-16 h and 7-14 days after experimental LAD occlusion or clinical onset of infarction (16)(17)(18)(19)(20)35).…”
Section: Tsupporting
confidence: 65%
“…Diagnosis of chronic infarction is not difficult (Bodenheimer et al, 1975(Bodenheimer et al, , 1976Hillis and Braunwald, 1977;Selwyn er al., 1977). Tomoscintigraphic studies have demonstrated a high degree of accuracy in estimation of the stage and size of acute and chronic myocardial infarction (Botvinick et al, 1975;Eichstaedt et al, 1980;Kronenberg et al, 1979;Momson et al, 1980;Wackers et al, 1977). Both M-mode echocardiography (Rasmussen and Corya, 1975) and two-dimensional techniques (Grube er al., 1979;Hecht et al, 1980;Parisi et al, 1981) have proved helpful in estimation of infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were interpreted as supporting the proposed role of tissue calcification in concentration of the agent, but as not excluiding the possibility of other mechanisms (3)(4)(5)(6). Other reports (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) have confirmed the dependence of 99mTc-P concentration on the presence of myocardial necrosis, and the importance of blood flow for modulating the level of 99mTc-P uiptake. Previous studies from our own and other laboratories, however, have not resolved certain important questions regarding 99mTc-P uptake after myocardial injury.…”
mentioning
confidence: 87%